CONSTRUCTIVIST LEARNING MODEL FOR MORAL CHARACTER AND PERFORMANCE IN UNIVERSITY - Dalman, Dalman; Mardiana, Mardiana (Universitas Muhammadiyah Semarang, 2018)
University is one of the educational providers who establish experts for the future. Especially for the teacher education major is always needed innovation in learning. Related to this case, a learning model for increasing creativity of students in transfering knowledge and skills possessed is needed. Constructivist and collaborative learning models can assist students in developing character education (moral character and performance).The method used interpretative method, some literatures related to interpreting, it was analyszed into a learning concept. The elements of constructivist are put in the lesson study steps.Keyword: Contructivist, Character.